WPŁYW OBRAZÓW KOŚCIOŁA NA TRYNITARNĄ WRAŻLIWOŚĆ CHRZEŚCIJAN Dokument Ku wspólnej wizji Kościoła w świetle eklezjologii prawosławnej - Leśniewski, Krzysztof (Studia Oecumenica, 2014)
The mystery of the Church is one of the most important problems in the modern ecumenical movement. Christians from various ecclesial traditions together reflect on what the Church is and what is its mission in the world and for the world. One of the fruits of ecumenical reflection on the Church is the document The Church: Towards a Common Vision of the Faith and Order Commission of the World Council of Churches (2013). In this article there were analyzed the most essential images of the Church, namely: Fellowship/Communion (Gr. koinonia), People of God, Body of Christ and Temple of the Holy Spirit, based on the above specified WCC document and the essential premises of Orthodox ecclesiology. The vision of the Church in view of the Trinitarian dogma is helpful in shaping the Trinitarian sensitivity of believers and raising their awareness that God in the Trinity of the Most Holy Persons is the basis of the unity of all Christians.